ANALISIS PENGUMUMAN PEMBAYARAN DEVIDEN TERHADAP ABNORMAL RETURN SAHAM PADA PERUSAHAAN LQ 45 DI BURSA EFEK INDONESIA - Hidayat, Riskin; Mukhlisin, Muhammad (Potensio, 2009)
AbstractThe purpose of this study is to see the stock market reaction to an event (event) dividend payment announcement abnormal return approach, the average abnormal stock return and Trading Volume Activity (TVA) before and after the dividend announcement on companies that make dividend payments. This study uses event study approach, to see the abnormal return by way of observing the stock market during the window period is 20 days before and 20 days after the event. Method of sampling using purposive sampling that sample selection based on certain criteria and acquired 26 companies that make the announcement of dividends paid in 2007. Results showed that there is a significant abnormal return occurs on day t-17, T-10, t-2, t +1, t +5 and this means that the announcements have information content of dividend payments so that the market reacted to the announcement, as evidenced by obtaining a significant abnormal return. In addition the research also shows that announcements of dividend payments make a difference on average abnormal stock returns significantly between before and after the event. Another result of this research is that there are differences in Trading Volume Activity significantly between before and after the announcement of events paying dividends.Keyword: Dividend, Abnormal return, Efficiency market